Effectiveness of Sachets in Modifying Rural Consumers' Buying Behavior and their Consumption Pattern-A Researcher's View - Sakkthivel, A. M.; Mishra, Bishnupriya (Indian Journal of Marketing, 2005)
The recent news from boardrooms of all companies ranging from cars to shampoos, are chanting only one 'mantra', how to focus and woo rural consumers to buy products/services?. In recent days, rural India has been witnessing a sea change in all aspects, needless to say the increase of standard of living and catching up with new life styles. Thanks to private satellite channels, they bring the world courtyards of many village houses. This created a tremendous modification in the behavior of rural consumers. Also, many rural youth usually go out of their places for higher education, which proves to be a leverage to face new life styles in semi-urban and metros. Many companies like Hindustan Lever Limited already made inroads into rural areas to establish their markets and fairly succeeded in their efforts. Hindustan Lever Limited created a group called 'Self Help Group'. The main motto of the group is to identify unemployed educated youths and housewives from different villages and provide them a small fund to setup shops in front of their houses to sell products (mainly from HLL).It serves a dual purpose of developing entrepreneurship in rural markets areas and to promote HLL products as well. Not only FMCG's but many consumer durable companies found rural markets very potential and made inroads into this lucrative market. This vividly shows the potential of rural markets that were long neglected which now came into limelight with a force to reckon with. Hence, rural marketing finds a prominent place in every company's marketing map and everyone wants to have a competitive edge in this arena. This paper was mainly developed on the basis of the primary survey conducted among the rural consumers in certain parts of Karnataka to analyze the role of FMCG products (in sachets) in boosting rural consumers' consumption pattern and the modification of their buying behavior.